If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -99 = 11 Reorder the terms: -99 + 11x = 11 Solving -99 + 11x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '99' to each side of the equation. -99 + 99 + 11x = 11 + 99 Combine like terms: -99 + 99 = 0 0 + 11x = 11 + 99 11x = 11 + 99 Combine like terms: 11 + 99 = 110 11x = 110 Divide each side by '11'. x = 10 Simplifying x = 10
| 8x+6=6(x+7) | | 0.3x-5=0.1(x+10) | | 3x^2-39x=0 | | Y-9-y+5=8y | | 1200=7v*v+300 | | y=7v*v+300 | | .4x+.6y=24 | | 13m^2+39m=0 | | sx+ty=u | | z^4-1=0 | | x-9/2-3=x-8/3 | | 11x/14-9=x/7+36 | | x/4+x/5=9/20 | | 0=-16t^2+vt+c | | 2n/3-7/13=31/39 | | 4c+1=32 | | x/4-3=-8 | | 9(z+3)-2(z-4)=3(z-4)+3(z-1) | | 9(z+3)-2(z-4)=3(z-1) | | 2x^3+x-18=0 | | -9x+4y=14 | | X^2=y+12 | | 8x=36x | | 500-335= | | 48t^2-28t+2=0 | | 2x^2+10x=-6 | | -41=-2-13n | | 0=36p^2-31 | | 4x*2+8x-32=0 | | 0=36p^2-9 | | 40=36p^2-9 | | 9x*2-21=0 |